Carbon-coated lithium iron phosphate positive electrode material and preparation method thereof

By covering the carbon layer on the surface of lithium iron phosphate particles and using deionized water and special binders, the low conductivity of lithium iron phosphate positive electrode materials and the pollution of traditional solvent systems is solved, and efficient battery performance improvement and environmental protection are achieved Production.

CN119447302AActive Publication Date: 2025-02-14JIANGSU OLITER ENERGY TECH CO LTD

Patent Information

Application Number
CN202411586632.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing lithium-ion battery cathode material lithium iron phosphate has problems such as low tap density, low electronic conductivity, and small lithium ion diffusion efficiency. The traditional organic solvent system is volatile, flammable and explosive, high toxicity, and polluting the environment. Disadvantages, the adhesive strength of the adhesive also needs to be improved.

Method used

Carbon-coated lithium iron phosphate positive electrode material and its preparation method are adopted. By covering a carbon layer on the surface of lithium iron phosphate particles, the conductive properties of the material are improved, and deionized water is used as a solvent, combined with a special binder, the positive electrode material is enhanced. Adhesion to aluminum foil.

Benefits of technology

The tap density, electronic conductivity and lithium ion diffusion efficiency of the positive electrode material are improved, the adhesion of the adhesive is enhanced, the cycle life and conductivity of the battery are improved, and the production cost is reduced and environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124439900000031
    Figure BDA0005124439900000031
  • Figure BDA0005124439900000041
    Figure BDA0005124439900000041
  • Figure BDA0005124439900000042
    Figure BDA0005124439900000042
Patent Text Reader

Abstract

The invention discloses a carbon-coated lithium iron phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of electrochemical energy materials. The preparation method comprises the following steps: stirring a binder and 80% of a solvent in parts by weight at 50-55 DEG C, adding a conductive agent, and stirring at the temperature lower than 40 DEG C for 2 hours; adding carbon-coated lithium iron phosphate, stirring, adding 20% of a solvent, and stirring; vacuumizing, maintaining the pressure, breaking the vacuum again, vacuumizing again, stirring, and testing the viscosity to obtain positive electrode slurry; and coating on an aluminum foil, and rolling to obtain the positive electrode material. The interior of the binder is of a firm three-dimensional network cross-linked structure, and meanwhile, the binder contains a benzotriazole structure and rich hydroxyl groups, so that the binder is high in adhesive force, and the non-polar part of the binder is beneficial to wetting an electrode by an electrolyte; and the binder and other raw materials have good compatibility, synergistically play a role, and jointly endow the carbon-coated lithium iron phosphate positive electrode material with excellent and stable cycle life, conductivity and the like, so that the carbon-coated lithium iron phosphate positive electrode material has excellent comprehensive performance and is safer to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy materials, and in particular, relates to a carbon-coated lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion battery is a highly efficient energy storage device with a wide range of applications. Its development trend is towards higher energy density, ultra-long cycle life and high safety. As one of the positive electrode materials of lithium-ion batteries, lithium iron phosphate is currently the most widely used positive electrode material. It has attracted much attention from the industry, especially due to its ultra-long cycle life, outstanding safety and low production cost. However, lithium iron phosphate materials also have disadvantages such as low tap density, low electronic conductivity and low lithium ion diffusion efficiency. In order to overcome the shortcomings of lithium iron phosphate positive electrode materials, people have done a lot of research work to improve their conductivity by modifying lithium iron phosphate materials. For example, a layer of conductive materials such as carbon, manganese and cobalt is coated and doped on the surface of lithium iron phosphate particles. Among them, surface carbon coating is an important means of modifying lithium iron phosphate positive electrode materials.

[0003] At present, in the industrial production of lithium-ion batteries, polyvinylidene fluoride (PVDF) is mostly used as a binder, and organic small molecules such as N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF) are used as dispersants. Although the organic solvent system has good dispersibility, it has the disadvantages of being volatile, flammable and explosive, and highly toxic. The volatilization of organic solvents seriously pollutes the environment and seriously affects the health of workers. At the same time, the production cost of organic solvent systems remains high. Chinese patent CN105428658A discloses a water-based binder positive electrode material for lithium iron phosphate batteries and a preparation method thereof. The invention uses deionized water as a dispersant, and the binder used is carboxymethyl chitosan and polyethylene glycol (PEG) in a weight ratio of (2.8-3.3): 1. Although the cost is greatly reduced and the battery performance is improved, the bonding force of the binder still needs to be improved.

[0004] In addition, most of the existing technologies have poor adhesion between the positive electrode slurry and the aluminum foil, which leads to problems such as material falling off, powder shedding, poor overall flexibility of the positive electrode plate, and reduced unit volume energy density of the plate, all of which are not conducive to the performance of the final finished battery.

[0005] Therefore, it is urgent to design and prepare a carbon-coated lithium iron phosphate positive electrode material to meet different market demands. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a carbon-coated lithium iron phosphate positive electrode material and a preparation method thereof.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a carbon-coated lithium iron phosphate positive electrode material comprises the following steps:

[0009] Weigh 90-95 parts of carbon-coated lithium iron phosphate, 2-6 parts of conductive agent, 2-6 parts of binder and 75-80 parts of solvent by weight;

[0010] First, the binder and 80% solvent are mixed and stirred at 50-55°C for 3h, and then the conductive agent is added and stirred at below 40°C for 2h, followed by the addition of carbon-coated lithium iron phosphate and continued stirring for 3h, followed by the addition of 20% solvent and continued stirring for 2h, and then the system is evacuated and pressure maintained for 10min, and then the vacuum is broken, and then evacuated again and continued to stir for 40min until the foam is completely eliminated, and the viscosity is tested to obtain a positive electrode slurry with a viscosity of 3000-4000mPa·s, and finally the positive electrode slurry is coated on aluminum foil, and then roller pressing is performed to obtain a carbon-coated lithium iron phosphate positive electrode material.

[0011] Furthermore, the carbon-coated lithium iron phosphate is prepared by the following steps:

[0012] First, lithium nitrate, phosphoric acid, ferric chloride and glucose were dissolved in deionized water respectively; then, lithium nitrate solution, phosphoric acid solution, ferric chloride solution and glucose solution were slowly added to deionized water in turn, stirred thoroughly until completely mixed, and then rotary evaporated at 100°C to obtain a precursor, and the precursor was heated to 200°C at 5°C / min and calcined for 2h, and then heated to 800°C at 2°C / min under nitrogen protection and calcined for 3h, and finally naturally cooled to room temperature to obtain carbon-coated lithium iron phosphate; the dosage ratio of lithium nitrate, phosphoric acid, ferric chloride and glucose was 1.8g:2.2g:3.9g:10.8g.

[0013] Carbon-coated lithium iron phosphate improves the tap density, electronic conductivity and lithium ion diffusion efficiency of the positive electrode material. In addition, the carbon source of carbon-coated lithium iron phosphate is obtained by carbonization of glucose, so the surface of carbon-coated lithium iron phosphate has abundant carboxyl and hydroxyl groups, while the surface of the binder has abundant hydroxyl groups. Therefore, carbon-coated lithium iron phosphate and the binder can produce hydrogen bond interactions in deionized water, thereby improving the compatibility and dispersion of the two in the positive electrode slurry, which can further improve the corresponding performance of the positive electrode material.

[0014] Furthermore, the conductive agent is one or more of acetylene black, carbon black, Ketjen black, and carbon nanotubes.

[0015] Furthermore, the binder is prepared by the following steps:

[0016] S1. Replace the air in a dry three-necked flask with nitrogen, then add epichlorohydrin and chloroform in sequence, stir thoroughly and heat to 65°C, then slowly add a mixed solution of benzotriazole and chloroform, react at 65°C for 3h after the addition is complete, cool to room temperature after the reaction is complete, distill under reduced pressure, purify by column chromatography (a mixed solvent of chloroform and ether is selected as the eluent, and the volume ratio of chloroform to ether is 9:1), and distill under reduced pressure to obtain intermediate 1; the dosage ratio of benzotriazole, epichlorohydrin and chloroform is 12.5g:7.8mL:120mL;

[0017] The molar ratio of benzotriazole to epichlorohydrin is controlled to be 1:1 and benzotriazole is slightly excessive. Under heating conditions, the amino group of benzotriazole and the epoxy group of epichlorohydrin undergo addition reaction. The reaction process is as follows:

[0018]

[0019] S2. Replace the air in the dry three-necked flask with nitrogen, then add D-glucosamine, triethylamine and dimethyl sulfoxide in sequence, stir and dissolve, heat to 80°C, slowly add the mixed solution of intermediate 1 and dimethyl sulfoxide, react at 80°C for 3h after the addition, cool to room temperature after the reaction, and distill under reduced pressure to obtain intermediate 2; the dosage ratio of D-glucosamine, intermediate 1, triethylamine and dimethyl sulfoxide is 18.4g:19g:16.3mL:180mL;

[0020] Triethylamine is used as an acid-binding agent, and the molar ratio of D-glucosamine to intermediate 1 is controlled to be 1.1-1.2:1. -NH2 of D-glucosamine and -Cl of intermediate 1 undergo substitution reaction. The reaction process is shown below:

[0021]

[0022] S3, under nitrogen protection, trimethylolpropane triacrylate, DBU (1,8-diazobisspiro[5.4.0]undec-7-ene) and dimethyl sulfoxide were added into a three-necked flask, stirred evenly and then heated to 70°C, then intermediate 2 was slowly added, and after the addition was completed, the mixture was reacted at 70°C for 18 hours. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 3; the dosage ratio of intermediate 2, trimethylolpropane triacrylate, DBU and dimethyl sulfoxide was 32.6 g:22.9 mL:0.4 g:200 mL;

[0023] Under the catalytic action of DBU, the molar ratio of intermediate 2 to trimethylolpropane triacrylate is controlled to be 1.05-1.1:1, and intermediate 2 and trimethylolpropane triacrylate undergo Michael addition reaction. The reaction process is as follows:

[0024]

[0025] S4. Bubble nitrogen into deionized water for 0.5h to remove oxygen in the deionized water, then add carboxymethyl cellulose, stir thoroughly to obtain a clear and viscous reaction solution for use; then add intermediate 3, acrylic acid, butyl acrylate, N-hydroxyacrylamide and ammonium persulfate to the reaction solution, stir and react at 60°C for 6h, cool to room temperature after the reaction, slowly add sodium hydroxide solution to adjust the pH of the system to 6, and obtain a binder; the amount ratio of carboxymethyl cellulose, intermediate 3, acrylic acid, butyl acrylate, N-hydroxyacrylamide and ammonium persulfate is 1g:2.6g:4mL:1g:0.2g:0.15g.

[0026] Under the action of ammonium persulfate, the carbon-carbon double bonds on the intermediate 3 react chemically with the carbon-carbon double bonds on acrylic acid, butyl acrylate, and N-hydroxyacrylamide to polymerize, and then form a strong three-dimensional network cross-linked structure with carboxymethyl cellulose. In addition, there are abundant polar hydroxyl groups on the binder, so the binder of the present invention has excellent adhesion and can effectively improve the performance and life of the finished battery.

[0027] The binder contains a benzotriazole structure, whose three nitrogen atoms are parallel to the benzene ring, which has a strong coordination ability and can form a stable complex with the aluminum on the aluminum foil current collector through coordination bonds, which allows the positive electrode slurry to adhere to the aluminum foil for a long time and is not easy to fall off, thereby making the internal current transmission of the battery smoother. The benzene ring on the intermediate 3 and the butyl group of butyl acrylate both provide non-polar parts for the binder, which helps the electrolyte wet the electrode. The electrolyte wets the electrode by improving the wettability of the electrode material and optimizing the distribution and reaction kinetics of the electrolyte on the electrode, thereby improving the performance, cycle life and capacity of the battery.

[0028] The abundant hydroxyl groups on the binder make the binder compatible with the other raw materials of the positive electrode slurry, and each raw material of the positive electrode material can fully play its role, so that the carbon-coated lithium iron phosphate positive electrode material of the present invention has excellent and stable cycle life and conductive properties.

[0029] Furthermore, the solvent is deionized water.

[0030] The present invention also discloses a carbon-coated lithium iron phosphate positive electrode material, which is prepared according to the above-mentioned method for preparing a carbon-coated lithium iron phosphate positive electrode material.

[0031] The beneficial effects of the present invention are as follows: the interior of the binder of the present invention is a strong three-dimensional network cross-linked structure, and contains a benzotriazole structure and abundant hydroxyl groups, so the binder has strong adhesion, and the non-polar part of the binder helps the electrolyte to wet the electrode; the binder and the other raw materials have good compatibility and work synergistically, which together give the carbon-coated lithium iron phosphate positive electrode material of the present invention excellent and stable cycle life and conductive properties, etc., making it have excellent comprehensive performance and safer to use. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] Preparation of carbon-coated lithium iron phosphate, the specific steps are as follows:

[0035] 1.8 g of lithium nitrate was dissolved in 80 mL of deionized water; 2.2 g of phosphoric acid was dissolved in 30 mL of deionized water, and 3.9 g of ferric chloride was dissolved in 60 mL of deionized water; 10.8 g of glucose was dissolved in 30 mL of deionized water; the lithium nitrate solution, phosphoric acid solution, ferric chloride solution and glucose solution were slowly added to 100 mL of deionized water in sequence, stirred thoroughly until completely mixed, and then rotary evaporated at 100 ° C to obtain a precursor, the precursor was heated to 200 ° C at 5 ° C / min and calcined for 2 h, and then heated to 800 ° C at 2 ° C / min under nitrogen protection and calcined for 3 h, and finally naturally cooled to room temperature to obtain carbon-coated lithium iron phosphate.

[0036] Example 2

[0037] Prepare the binder, the specific steps are as follows:

[0038] S1. Replace the air in a 250 mL dry three-necked flask with nitrogen, then add 7.8 mL of epichlorohydrin and 80 mL of chloroform in sequence, stir thoroughly and heat to 65°C, then slowly add a mixed solution of 12.5 g of benzotriazole and 40 mL of chloroform, react at 65°C for 3 h after the addition is complete, cool to room temperature after the reaction is completed, distill under reduced pressure, purify by column chromatography (a mixed solvent of chloroform and ether is selected as the eluent, and the volume ratio of chloroform to ether is 9:1), and distill under reduced pressure to obtain intermediate 1;

[0039] S2, replace the air in a 500mL dry three-necked flask with nitrogen, then add 18.4g D-glucosamine, 16.3mL triethylamine and 140mL dimethyl sulfoxide in sequence, stir to dissolve and then heat to 80°C, then slowly add a mixed solution of 19g intermediate 1 and 40mL dimethyl sulfoxide, react at 80°C for 3h after the addition is complete, cool to room temperature after the reaction is completed, and distill under reduced pressure to obtain intermediate 2;

[0040] S3, under nitrogen protection, add 22.9 mL of trimethylolpropane triacrylate, 0.4 g of DBU and 200 mL of dimethyl sulfoxide into a 500 mL three-necked flask, stir evenly and heat to 70°C, then slowly add 32.6 g of intermediate 2, react at 70°C for 18 h after the addition is complete, cool to room temperature after the reaction is completed, and distill under reduced pressure to obtain intermediate 3;

[0041] S4. Bubble nitrogen into 120 mL of deionized water for 0.5 h to remove oxygen in the deionized water, then add 1 g of carboxymethyl cellulose and stir thoroughly to obtain a clear and viscous reaction solution for use; then add 2.6 g of intermediate 3, 4 mL of acrylic acid, 1 g of butyl acrylate, 0.2 g of N-hydroxyacrylamide and 0.15 g of ammonium persulfate to the reaction solution, stir and react at 60 ° C for 6 h, cool to room temperature after the reaction is completed, slowly add sodium hydroxide solution to adjust the pH of the system to 6, and obtain a binder.

[0042] Example 3

[0043] The carbon-coated lithium iron phosphate positive electrode material is prepared in the following specific steps:

[0044] According to the weight of each raw material, first, 2 parts of the binder prepared in Example 2 and 60 parts of deionized water are mixed and stirred at 50°C for 3 hours, then 1 part of acetylene black and 1 part of carbon black are added, and the mixture is stirred at below 40°C for 2 hours. Subsequently, 90 parts of the carbon-coated lithium iron phosphate prepared in Example 1 are added and the stirring is continued for 3 hours. Subsequently, 15 parts of deionized water are added and the stirring is continued for 2 hours. Then, the system is evacuated and the pressure is maintained for 10 minutes, and the vacuum is broken. Then, the system is evacuated again and the stirring is continued for 40 minutes until the foam is completely eliminated. The viscosity is tested to obtain a positive electrode slurry with a viscosity of 3000 to 4000 mPa·s. Finally, the positive electrode slurry is coated on aluminum foil, and then roller pressing is performed to obtain a carbon-coated lithium iron phosphate positive electrode material.

[0045] Example 4

[0046] The carbon-coated lithium iron phosphate positive electrode material is prepared in the following specific steps:

[0047] According to the weight of each raw material, first, 5 parts of the binder prepared in Example 2 and 62.4 parts of deionized water were mixed and stirred at 53°C for 3 hours, and then 3 parts of carbon black and 2 parts of Ketjen black were added, and the mixture was stirred at below 40°C for 2 hours. Subsequently, 93 parts of the carbon-coated lithium iron phosphate prepared in Example 1 were added and the stirring was continued for 3 hours. Subsequently, 15.6 parts of deionized water were added and the stirring was continued for 2 hours. Then, the system was evacuated and the pressure was maintained for 10 minutes, and the vacuum was broken. Then, the system was evacuated again and the stirring was continued for 40 minutes until the foam was completely eliminated. The viscosity was tested to obtain a positive electrode slurry with a viscosity of 3000 to 4000 mPa·s. Finally, the positive electrode slurry was coated on aluminum foil, and then roller pressing was performed to obtain a carbon-coated lithium iron phosphate positive electrode material.

[0048] Example 5

[0049] The carbon-coated lithium iron phosphate positive electrode material is prepared in the following specific steps:

[0050] According to the weight of each raw material, first, 6 parts of the binder prepared in Example 2 and 64 parts of deionized water are mixed and stirred at 55°C for 3 hours, then 2 parts of acetylene black, 2 parts of carbon black, and 2 parts of carbon nanotubes are added, and the mixture is stirred at below 40°C for 2 hours. Subsequently, 95 parts of the carbon-coated lithium iron phosphate prepared in Example 1 are added and the stirring is continued for 3 hours. Subsequently, 16 parts of deionized water are added and the stirring is continued for 2 hours. Then, the system is evacuated and the pressure is maintained for 10 minutes, and the vacuum is broken. Then, the system is evacuated again and the stirring is continued for 40 minutes until the foam is completely eliminated. The viscosity is tested to obtain a positive electrode slurry with a viscosity of 3000 to 4000 mPa·s. Finally, the positive electrode slurry is coated on aluminum foil, and then roller pressing is performed to obtain a carbon-coated lithium iron phosphate positive electrode material.

[0051] Comparative Example 1

[0052] The carbon-coated lithium iron phosphate positive electrode material is prepared in the following specific steps:

[0053] The remaining steps remain unchanged, except that the binder in Example 3 is replaced by untreated carboxymethyl cellulose, thereby preparing a carbon-coated lithium iron phosphate positive electrode material.

[0054] Performance Testing

[0055] The positive electrode materials prepared in Examples 3-5 and Comparative Example 1 were cut into small pieces of 4*10 cm and subjected to a peel strength test on a peel strength tester. The test results are shown in Table 1 below:

[0056] Table 1

[0057] Test items Example 3 Example 4 Example 5 Comparative Example 1 Peel strength N / m 3.83 3.98 4.21 3.51

[0058] The carbon-coated lithium iron phosphate positive electrode materials prepared in Examples 3-5 and Comparative Example 1 were respectively made into lithium iron phosphate batteries, and the following performance tests were carried out.

[0059] (1) Safety performance test of lithium iron phosphate battery: The battery passed the overcharge, over-discharge and puncture test according to GB / T 31485-2015 standard.

[0060] (2) The lithium iron phosphate battery cycle performance test was carried out according to GB / T 31484-2015 standard; the results are shown in Table 2 below:

[0061] Table 2

[0062]

[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-coated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Weigh 90-95 parts of carbon-coated lithium iron phosphate, 2-6 parts of conductive agent, 2-6 parts of binder and 75-80 parts of solvent by weight; stir the binder and 80% of the solvent at 50-55°C, add the conductive agent, stir for 2 hours at below 40°C, add the carbon-coated lithium iron phosphate, stir for 3 hours, add 20% of the solvent, stir for 2 hours, evacuate the system and maintain the pressure, break the vacuum, evacuate again and stir for 40 minutes, test the viscosity to obtain a positive electrode slurry, coat it on aluminum foil, and roll it to obtain a carbon-coated lithium iron phosphate positive electrode material; Wherein, the binder is prepared by the following steps: S1. Replace the air in the bottle with nitrogen, add epichlorohydrin and chloroform, stir and heat to 65°C, add benzotriazole and chloroform, react at 65°C for 3h, cool, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 1; S2, replace the air in the bottle with nitrogen, add D-glucosamine, triethylamine and dimethyl sulfoxide, stir and heat to 80°C, add intermediate 1 and dimethyl sulfoxide, react at 80°C for 3h, cool, and distill under reduced pressure to obtain intermediate 2; S3, under nitrogen protection, trimethylolpropane triacrylate, DBU and dimethyl sulfoxide were added to a flask, the temperature was raised to 70°C with stirring, intermediate 2 was added, the reaction was carried out at 70°C for 18 hours, the reaction was cooled, and the reaction was carried out under reduced pressure to obtain intermediate 3; S4. Bubble nitrogen into deionized water, add carboxymethyl cellulose, and stir to obtain a reaction solution; add intermediate 3, acrylic acid, butyl acrylate, N-hydroxyacrylamide and ammonium persulfate to the reaction solution, react at 60° C. for 6 hours, cool, add sodium hydroxide solution to adjust the pH of the system to 6, and obtain a binder.

2. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: Carbon-coated lithium iron phosphate is prepared by the following steps: First, lithium nitrate, phosphoric acid, ferric chloride, and glucose are dissolved in deionized water respectively; then lithium source solution, phosphorus source solution, iron source, and carbon source are added to deionized water in sequence, stirred, and rotary evaporated to obtain a precursor, which is calcined at 200°C for 2h, and then calcined at 800°C for 3h under nitrogen protection, and cooled to obtain carbon-coated lithium iron phosphate.

3. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The usage ratio of benzotriazole, epichlorohydrin and chloroform in step S1 is 12.5 g:7.8 mL:120 mL.

4. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The usage ratio of D-glucosamine, intermediate 1, triethylamine and dimethyl sulfoxide in step S2 is 18.4 g:19 g:16.3 mL:180 mL.

5. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The usage ratio of intermediate 2, trimethylolpropane triacrylate, DBU and dimethyl sulfoxide in step S3 is 32.6 g:22.9 mL:0.4 g:200 mL.

6. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The usage ratio of carboxymethyl cellulose, intermediate 3, acrylic acid, butyl acrylate, N-hydroxyacrylamide and ammonium persulfate in step S4 is 1 g:2.6 g:4 mL:1 g:0.2 g:0.15 g.

7. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 2, characterized in that: The usage ratio of lithium nitrate, phosphoric acid, ferric chloride and glucose is 1.8g:2.2g:3.9g:10.8g.

8. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The conductive agent is one or more of acetylene black, carbon black, Ketjen black and carbon nanotubes.

9. The method for preparing a carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The solvent is deionized water.

10. A carbon-coated lithium iron phosphate positive electrode material, characterized in that: It is prepared according to the method for preparing a carbon-coated lithium iron phosphate positive electrode material according to any one of claims 1-9.

Citation Information

Patent Citations

  • Waterborne binder positive electrode material for lithium iron phosphate battery and preparation method therefor

    CN105428658A

  • Lithium-ion battery, battery pole piece and preparation method of battery pole piece

    CN108011076A

  • Aqueous lithium iron phosphate battery and positive electrode slurry thereof and preparation method of positive electrode slurry

    CN113809322A

  • Diaphragm for improving polarization discharge of lithium battery and preparation method thereof

    CN116487825A

  • Modified lithium ion battery positive electrode material and preparation method and application thereof

    CN116525771A

Cited By

  • High-performance lithium iron phosphate composite material and preparation method thereof

    CN119349559A

  • High-performance lithium iron phosphate composite material and preparation method thereof

    CN119349559B

  • High-performance lithium iron phosphate positive electrode material and preparation method thereof

    CN120622444A